Governance and Bank Performance: Does Bank Risk Matter ? - Estu Widarwati; Soni Karmila; Nunik Nurmalasari (ETIKONOMI, 2022)
Governance becomes a guideline for the banking management system and is essential for banking survival during regular economic crises. We investigate the impact of governance on performance in the Indonesians' conventional and examine the mediating role of bank risk in bank governance and performance relationship. The samples are 18 conventional banks listed on Indonesia Stock Exchange (IDX) from 2014 to 2021 and analyzed using panel data regression and sobel test. We find the risk of state-own bank higher than private bank and foreign bank that could leads to lower performance. Then the results indicate that board size and board age influence bank risk and bank performance. Banks should consider the board size for efficiency and also the maximum standard of their directors' age based on arguments related to innovation-based work productivity in the competitive banking industry. The subsequent exploration of banking governance research is needed by examining the differences in bank ownership and bank characteristics linked to bank risk which is strong evidence as mediation in this study.JEL Classification: G20, G30, G32, G34